STIMULASI BUKU TEMATIK SD/MI KELAS IV TEMA 3 UNTUKMENUMBUHKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA - Amikratunnisyah1; Andi Prastowo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The description of this article is based on the number of elementary school students who still do not have the ability to read and understand well. This article describes a study about the contents of the stimulation of thematic textbooks for SD./MI grade IV theme 3 to foster students' reading comprehension skills. The study described in this article used a descriptive qualitative approach. The type of research conducted was a document analysis research (documentary analysis) study. The documents analyzed were the thematic textbooks for grade IV students on theme 3 revised edition in 2017 which consisted of teacher books and student books. The main informants in the study were the teacher's book and the student's book. While the formal object of the study was the ability to read and understand. The results showed that the thematic textbooks for class IV theme 3 already contained stimuli in growing students' reading comprehension skills. The stimulation contained in this thematic textbook was in the form of commands that stimulate students to carry out activities to achieve reading comprehension skills.